Lithium ion battery positive electrode material and preparation method and application thereof

By mixing the lithium source, the lithium-ion battery positive electrode material precursor and the high-performance finished cathode material and the solid-phase sintering method, the problems of poor crystal form and poor circulation performance of the lithium-ion battery positive electrode material are solved, and the preparation of the high-performance cathode material is realized, which improves the overall performance of the battery and reduces production costs.

CN119503905APending Publication Date: 2025-02-25NINGBO FULI BATTERY MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411425822.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing lithium-ion battery cathode materials have problems of poor crystal form and poor circulation performance during the production process, and the traditional doping treatment increases costs but has limited effect.

Method used

By mixing the lithium source, the lithium-ion battery positive electrode material precursor and the high-performance finished positive electrode material as seeds, the solid phase sintering is carried out, and the reaction conditions are controlled to effectively control the production rate of the crystal nucleus, thereby preparing a high-performance lithium-ion battery positive electrode material.

Benefits of technology

This method can significantly improve the first Coulomb efficiency, first discharge specific capacity and 200 capacity retention rate of the positive electrode material of lithium-ion battery, improve the overall performance of the material, and simplify the process and reduce costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and provides a lithium ion battery positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: mixing a lithium source, a lithium ion battery positive electrode material precursor and a seed crystal to obtain a mixture; and calcining the mixture to obtain the catalyst. The seed crystal is the prepared lithium ion battery positive electrode material. The invention further discloses the lithium ion battery positive electrode material prepared according to the method and the lithium ion battery, the battery comprises a positive electrode, a negative electrode and electrolyte, and the positive electrode comprises the lithium ion battery positive electrode material. The finished lithium ion battery positive electrode material is introduced as the seed crystal to induce the production of the lithium ion battery positive electrode material; by controlling the reaction conditions, the seed crystals can effectively control the production rate of the crystal nucleus in the reaction process, so that the produced lithium ion battery positive electrode material has better performance. The preparation method is simple and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] As a new type of green electric energy, lithium-ion batteries have been widely used in 3C digital electronic products, power tools, electric vehicles, energy storage and other fields. Lithium-ion battery positive electrode materials are currently a hot spot for major companies to compete for development. Lithium-ion battery positive electrode materials include lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium-rich manganese-based and ternary positive electrode materials.

[0003] At present, lithium-ion power batteries have been widely used in new energy vehicles. Improving the energy density of automotive lithium-ion power batteries and alleviating travel anxiety are issues that urgently need to be addressed.

[0004] The traditional production method of lithium-ion battery positive electrode materials is to evenly mix the lithium battery precursor and lithium salt in a mixer, and then solid-phase sinter the mixture in a furnace to prepare the required lithium-ion battery positive electrode materials. In order to improve the electrical properties of lithium-ion battery positive electrode materials, metal oxides and rare earths are doped during the mixing process or surface coating is performed later. This treatment not only increases costs, but also cannot significantly improve the electrical properties of the materials.

[0005] Therefore, it is necessary to provide a method for preparing a lithium-ion battery positive electrode material with high initial efficiency, high capacity and good cycle performance, so as to solve the problems of poor crystal form and poor cycle performance of the lithium-ion battery positive electrode material. Summary of the invention

[0006] The present disclosure provides a lithium ion battery positive electrode material and a preparation method and application thereof, so as to at least solve the above technical problems existing in the prior art.

[0007] According to a first aspect of the present disclosure, there is provided a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:

[0008] S1: mixing a lithium source, a lithium ion battery cathode material precursor and a seed crystal to obtain a mixture;

[0009] S2: calcining the mixture in step S1 to obtain the positive electrode material for the lithium-ion battery;

[0010] The seed crystal is the prepared positive electrode material of the lithium-ion battery.

[0011] Specifically, the present invention uses the prepared lithium-ion battery positive electrode material as seed crystals to further induce the production of a large amount of lithium-ion battery positive electrode material. By controlling the reaction conditions, these seed crystals can effectively control the production rate of the crystal nucleus, so that the produced lithium-ion battery positive electrode material has better performance.

[0012] In one embodiment, the added amount of the seed crystals accounts for 0.02-2% of the total mass of the mixture.

[0013] In one embodiment, the lithium source is selected from at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium acetate, lithium oxide, and lithium citrate.

[0014] In one possible implementation, the lithium-ion battery positive electrode material precursor is selected from at least one of oxides, hydroxides, oxyhydroxides, and carbonates corresponding to one or more materials of nickel, cobalt, and manganese.

[0015] In one embodiment, the lithium ion battery positive electrode material precursor is selected from Ni 0.5 Co 0.2 Mn 0.3 (OH)2、Ni 1 / 6 Co 1 / 6 Mn 4 / 6 Either CO3, Co3O4.

[0016] In one possible implementation, the molar ratio of lithium in the lithium source to the total amount of nickel, cobalt and manganese in the lithium ion battery positive electrode material precursor is 1.0-1.5, that is, Li / Me=1.0-1.5.

[0017] In one embodiment, step S1 uses a mixer for mixing, and the mixing conditions are: first mixing at 5 to 10 Hz for 5 to 10 min, and then mixing at 30 to 35 Hz for 30 to 35 min.

[0018] In one embodiment, the calcination in step S2 is performed in an air or oxygen atmosphere, and the flow rate of the air or oxygen atmosphere is 0.5 to 3 L / min.

[0019] In one embodiment, the calcination conditions in step S2 include: raising the temperature to 800-1100°C at a heating rate of 0.2-10°C / min, and calcining for 6-20h; after the reaction is completed, reducing the temperature to room temperature at a rate of 1-10°C / min.

[0020] According to a second aspect of the present disclosure, a lithium ion battery positive electrode material prepared according to the above preparation method is provided.

[0021] According to a third aspect of the present disclosure, a lithium ion battery is provided, the lithium ion battery comprising a positive electrode, a negative electrode and an electrolyte; the positive electrode comprises the lithium ion battery positive electrode material prepared according to the above preparation method.

[0022] According to an implementable embodiment of the present disclosure, at least the following beneficial effects are achieved:

[0023] The present invention introduces a small amount of high-performance finished lithium-ion battery positive electrode material as a seed crystal to induce the production of lithium-ion battery positive electrode material, which can greatly improve the performance of the lithium-ion battery positive electrode material.

[0024] The present invention is to mix the lithium source, the precursor of the positive electrode material of the lithium ion battery and the seed crystals uniformly and then perform solid phase sintering, and control the reaction conditions. During the reaction, the seed crystals can effectively control the production rate of the crystal nucleus, so that the produced positive electrode material of the lithium ion battery has better performance. The preparation method of the present invention is simple and low in cost.

[0025] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. DETAILED DESCRIPTION

[0026] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0027] The first coulombic efficiency, first discharge specific capacity and 200-time capacity retention rate in the following embodiments are all tested by the prepared button cells. Specifically, the positive electrode material powders prepared as follows are used as active materials, and are mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) is used as a solvent, placed in a mixing tank, and placed in a high-speed homogenizer, stirred at a speed of 1200 r / min for 30 s, 2500 r / min for 120 s, and 1200 r / min for 30 s to obtain a slurry. Then use an automatic coating machine to coat the slurry on the current collector aluminum foil, lay it flat on the tempered glass, transfer it to a vacuum oven at 85℃ and dry it for 6 hours, punch it into a pole piece with a diameter of 14mm, and then place it in a vacuum drying oven at 105℃ and dry it for 4 hours. The button cell of CR2032 is assembled in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm. The battery uses a pure metal lithium sheet with a diameter of 16mm and a thickness of 0.5mm as the negative electrode, and a porous polyethylene film with a diameter of 18mm and a model of Celgard (produced by Celgard) as the diaphragm. After the battery is assembled, it is left to stand for 12 hours, and the charge and discharge test is carried out at different potentials according to the crystal form of the positive electrode material.

[0028] Example 1

[0029] In this example, a ternary cathode material, lithium nickel cobalt manganese oxide LiNi 0.5 Co 0.2 Mn 0.3 O2, the specific process is:

[0030] (1) Lithium carbonate Li2CO3 (Shanghai Zhongli Industrial Co., Ltd., the same below), nickel cobalt manganese hydroxide Ni 0.5 Co 0.2 Mn 0.3 (OH)2 (Ningbo Rongbai New Energy Technology Co., Ltd., the same below) and seed nickel cobalt manganese oxide LiNi 0.5 Co 0.2 Mn 0.3 O2 (Ningbo Rongbai New Energy Technology Co., Ltd.) was mixed in a high-speed mixer, first at a low speed of 5 Hz for 5 min, and then at a high speed of 35 Hz for 30 min to obtain a mixture; wherein Li2CO3 and Ni 0.5 Co 0.2 Mn 0.3 (OH)2 was mixed according to the molar ratio of Li / (Ni+Co+Mn) of 1.08, and the seed LiNi 0.5 Co 0.2 Mn 0.3 The amount of O2 added was 0.02% of the total mass of the mixture.

[0031] (2) placing the mixture of step (1) in a muffle furnace, heating the temperature to 930° C. at a rate of 5° C. / min in an oxygen atmosphere (flow rate of 2 L / min), and keeping the temperature for 16 h; after the reaction is completed, cooling the temperature to room temperature at a rate of 5° C. / min and taking out the mixture, thereby obtaining the ternary positive electrode material lithium nickel cobalt manganese oxide.

[0032] After testing, the final lithium battery ternary positive electrode material LiNi 0.5 Co 0.2 Mn 0.3 The electrical properties of O2 are: the first coulombic efficiency at 0.2C is ≥87%, and the test value is 87.5%; the first discharge specific capacity is ≥173.5mAh / g, and the test value is 174.0mAh / g; the capacity retention rate after 200 times is ≥99%.

[0033] Comparative Example 1

[0034] This comparative example prepared the ternary positive electrode material lithium nickel cobalt manganese oxide LiNi 0.5 Co 0.2 Mn 0.3 O2, the difference from Example 1 is that no seed crystal is added when preparing the mixture in this comparative example. The specific process is:

[0035] (1) Lithium carbonate Li2CO3 and nickel cobalt manganese hydroxide Ni 0.5 Co 0.2 Mn 0.3 (OH)2 was mixed in a high-speed mixer, first at a low speed of 5 Hz for 5 min, and then at a high speed of 35 Hz for 30 min to obtain a mixture; wherein Li2CO3 and Ni 0.5 Co 0.2 Mn 0.3 (OH)2 was mixed at a molar ratio of Li / (Ni+Co+Mn) of 1.08.

[0036] (2) placing the mixture of step (1) in a muffle furnace, heating the temperature to 930° C. at a rate of 5° C. / min in an oxygen atmosphere (flow rate of 2 L / min), and keeping the temperature for 16 h; after the reaction is completed, cooling the temperature to room temperature at a rate of 5° C. / min and taking out the mixture, thereby obtaining the ternary positive electrode material lithium nickel cobalt manganese oxide.

[0037] After testing, the final lithium battery ternary positive electrode material LiNi 0.5 Co 0.2 Mn 0.3 The electrical properties of O2 are: the first coulombic efficiency at 0.2C is ≥85%, and the test value is 85.5%; the first discharge specific capacity is ≥169mAh / g, and the test value is 170mAh / g; the capacity retention rate after 200 times is ≥95%.

[0038] Example 2

[0039] In this embodiment, lithium cobalt oxide LiCoO2, a positive electrode material for a lithium-ion battery, is prepared. The specific process is as follows:

[0040] (1) Lithium carbonate Li2CO3, cobalt oxide Co3O4 (Lanzhou Jinchuan New Materials Technology Co., Ltd., the same below) and seed lithium cobalt oxide LiCoO2 (Hunan Shanshan Energy Technology Co., Ltd.) were mixed in a high-speed mixer, first at a low speed of 5 Hz for 5 min, and then at a high speed of 35 Hz for 30 min to obtain a mixture; wherein Li2CO3 and Co3O4 were mixed at a molar ratio of Li / (Ni+Co+Mn) of 1.03, and the amount of seed LiCoO2 added accounted for 0.04% of the total mass of the mixture.

[0041] (2) placing the mixture of step (1) in a muffle furnace, heating the temperature to 1100° C. at a rate of 5° C. / min in an air atmosphere (flow rate of 2 L / min), and keeping the temperature for 18 h; after the reaction is completed, cooling the temperature to room temperature at a rate of 5° C. / min and taking out the mixture, thereby obtaining lithium cobalt oxide, a positive electrode material for lithium-ion batteries.

[0042] After testing, the electrical properties of the final lithium-ion battery positive electrode material lithium cobalt oxide LiCoO2 are as follows: the first coulomb efficiency at 0.1C is ≥94.0%, and the test value is 94.7%; the first discharge specific capacity is ≥184mAh / g, and the test value is 185.4mAh / g; and the capacity retention rate after 200 times is ≥99%.

[0043] Comparative Example 2

[0044] This comparative example prepares lithium cobalt oxide LiCoO2, a positive electrode material for lithium-ion batteries. The difference from Example 2 is that this comparative example does not add seed crystals when preparing the mixture. The specific process is:

[0045] (1) Lithium carbonate Li2CO3 and cobalt oxide Co3O4 are mixed in a high-speed mixer, first at a low speed of 5 Hz for 5 minutes, and then at a high speed of 35 Hz for 30 minutes to obtain a mixture; wherein Li2CO3 and Co3O4 are mixed at a molar ratio of Li / (Ni+Co+Mn) of 1.03.

[0046] (2) placing the mixture of step (1) in a muffle furnace, heating the temperature to 1100° C. at a rate of 5° C. / min in an air atmosphere (flow rate of 2 L / min), and keeping the temperature for 18 h; after the reaction is completed, cooling the temperature to room temperature at a rate of 5° C. / min and taking out the mixture, thereby obtaining lithium cobalt oxide, a positive electrode material for lithium-ion batteries.

[0047] After testing, the electrical properties of the final lithium-ion battery positive electrode material lithium cobalt oxide LiCoO2 are as follows: the first coulomb efficiency at 0.1C is ≥91.0%, and the test value is 91.5%; the first discharge specific capacity is ≥179mAh / g, and the test value is 180mAh / g; and the capacity retention rate after 200 times is ≥94%.

[0048] Example 3

[0049] In this example, a lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, the specific process is:

[0050] (1) Lithium carbonate Li2CO3, nickel cobalt manganese carbonate Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 (Ningbo Rich Lithium Battery Material Technology Co., Ltd., the same below) and seed lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 (Ningbo Fuli Battery Material Technology Co., Ltd.) was mixed in a high-speed mixer, first at a low speed of 5 Hz for 5 min, and then at a high speed of 35 Hz for 30 min to obtain a mixture; wherein Li2CO3 and Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was mixed according to the molar ratio of Li / (Ni+Co+Mn) of 1.4, and the seed Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The amount of O2 added was 0.5% of the total mass of the mixture.

[0051] (2) placing the mixture of step (1) in a muffle furnace, heating the temperature to 930° C. at a rate of 5° C. / min in an oxygen atmosphere (flow rate of 2 L / min), and keeping the temperature for 16 h; after the reaction is completed, cooling the temperature to room temperature at a rate of 5° C. / min to obtain a lithium-rich manganese-based positive electrode material.

[0052] After testing, the final lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The electrical properties of O2 are: the first coulombic efficiency at 0.1C (2.0~4.8V) is ≥86%, and the test value is 87%; the first discharge specific capacity is ≥280mAh / g, and the test value is 285mAh / g; the capacity retention rate after 200 times is ≥85%.

[0053] Comparative Example 3

[0054] In this comparative example, lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, the difference from Example 3 is that no seed crystal is added when preparing the mixture in this comparative example. The specific process is:

[0055] (1) Lithium carbonate Li2CO3 and nickel cobalt manganese carbonate Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was mixed in a high-speed mixer, first at a low speed of 5 Hz for 5 min, and then at a high speed of 35 Hz for 30 min to obtain a mixture; wherein Li2CO3 and Ni 1 / 6 Co 1 / 6 Mn 4 / 6CO3 is mixed at a molar ratio of Li / (Ni+Co+Mn) of 1.4.

[0056] (2) placing the mixture of step (1) in a muffle furnace, heating the temperature to 930° C. at a rate of 5° C. / min in an oxygen atmosphere (flow rate of 2 L / min), and keeping the temperature for 16 h; after the reaction is completed, cooling the temperature to room temperature at a rate of 5° C. / min to obtain a lithium-rich manganese-based positive electrode material.

[0057] After testing, the final lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The electrical properties of O2 are as follows: the first coulombic efficiency at 0.1C (2.0-4.8V) is ≥84.0%, and the test value is 85%; the first discharge specific capacity is ≥275mAh / g, and the test value is 280mAh / g; the capacity retention rate after 200 times is ≥82%.

[0058] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solution of this disclosure can be achieved, and this document is not limited here.

[0059] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0060] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A method for preparing a positive electrode material for a lithium ion battery, characterized in that: The following steps are involved: S1: mixing a lithium source, a lithium ion battery cathode material precursor and a seed crystal to obtain a mixture; S2: calcining the mixture in step S1 to obtain the positive electrode material for the lithium-ion battery; The seed crystal is the prepared positive electrode material of the lithium-ion battery.

2. The preparation method according to claim 1, characterized in that: The added amount of the seed crystals accounts for 0.02-2% of the total mass of the mixture.

3. The preparation method according to claim 1, characterized in that: The lithium source is selected from at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium acetate, lithium oxide and lithium citrate.

4. The preparation method according to claim 1, characterized in that: The lithium-ion battery positive electrode material precursor is selected from at least one of oxides, hydroxides, oxyhydroxides, and carbonates corresponding to one or more materials selected from nickel, cobalt, and manganese; Preferably, the lithium-ion battery cathode material precursor is selected from Ni 0.5 Co 0.2 Mn 0.3 (OH)2、Ni 1 / 6 Co 1 / 6 Mn 4 / 6 Either CO3, Co3O4.

5. The preparation method according to claim 4, characterized in that: The molar ratio of lithium in the lithium source to the total amount of nickel, cobalt and manganese in the lithium ion battery positive electrode material precursor is 1.0 to 1.

5.

6. The preparation method according to claim 1, characterized in that: In step S1, a mixer is used for mixing, and the mixing conditions are: first mixing at 5 to 10 Hz for 5 to 10 min, and then mixing at 30 to 35 Hz for 30 to 35 min.

7. The preparation method according to claim 1, characterized in that: Step S2: calcining is performed in air or oxygen atmosphere, and the flow rate of the air or oxygen atmosphere is 0.5 to 3 L / min.

8. The preparation method according to claim 7, characterized in that: The calcination conditions in step S2 include: increasing the temperature to 800-1100° C. at a heating rate of 0.2-10° C. / min, and calcining for 6-20 hours; after the reaction is completed, reducing the temperature to room temperature at a rate of 1-10° C. / min.

9. A lithium-ion battery positive electrode material obtained according to the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte; the positive electrode comprises a lithium-ion battery positive electrode material prepared by the preparation method according to any one of claims 1 to 8.